During-the-Event - Wall, Roger, 1955- (Book collections on Project MUSE., 2019)
In the near future, climate change has ravaged the United States, leading the government to overcorrect through culls and relocation. Those who survive the mandated destruction are herded into "habitable production zones," trading their freedom for illusions of security. The few who escape learn quickly that the key to survival is to stay hidden in the corners of the country. For seventeen years, During-the-Event, or D.E., has lived free in a pastoral life with his grandfather in North Dakota. But when death reaches their outpost. D.E. is forced on a journey that will change his life--and reveal surprises about his past.